The EC (Electro Conductivity) Value of Plant Age for Green Leaf Lettuce (Lactuca sativa L.) Using NFT (Nutrient Film Technique) Hydroponic Systems - Ni Nyoman Padang Cakra Binaraesa; Sandra Malin Sutan; Ary Mustofa Ahmad (Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2016)
This study in September 2016 to November 2016 at the Institute for Agricultural Technology Jawa Timur, Jl. Kingdom Karangploso KM 4, Malang. This study aims to determine the relationship with the large volume hydroponic nutrient value of EC (electro conductivity) and know the value of EC (electro-conductivity) based on the age of the green leaf lettuce plants with NFT hydroponics system. EC treatment used in the study, namely 1200, 1500, 1800 and 2100 μs / cm with the pH of the solution is always controlled ranged from 5.5 to 5.8. The results showed that the relationship with large volume hydroponic nutrient EC value is proportional and showed a linear graph. Yields of lettuce plants with the parameters of the long end of the plant, plant height, leaf number, root length, root mass and the mass of the plant with the plant without roots showed the best results with the treatment of EC 1800 μs / cm. Great value EC berdarkan age of the plant to get the lettuce crop yields good ie aged 5 days ie 1200 μS / cm, 10 days at 2100 μS / cm and at the age of 15 days to 35 days ie 1800 μS / cm. Keywords: EC, Hydroponics, hydroponic nutrients, NFT, pH, Lettuce